2018
DOI: 10.1152/ajpendo.00119.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal high-fat diet on key components of the placental and hepatic endocannabinoid system

Abstract: Maternal obesity in pregnancy has been linked to a spectrum of adverse developmental changes. Involvement of eCBs in obesity is well characterized. However, information regarding eCB physiology in obesity associated with pregnancy is sparse. This study evaluated fetomaternal hepatic, systemic, and placental eCB molecular changes in response to maternal consumption of a HFD. From ≥9 mo before conception, nonpregnant baboons ( Papio spp.) were fed a diet of either 45 (HFD; n = 11) or 12% fat or a control diet (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…However, of note, the present study focused on the regulation of the protein content of ECS components instead of transcript levels. Another study recently published by Gandhi et al ., showed that maternal HF diet in baboons decreases CB2 and FAAH protein content in fetal liver, but the impact of ECS changes on liver morphology and function was not investigated 48 . The different profiles found in liver ECS among these studies may arise from different ages and species used in the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, of note, the present study focused on the regulation of the protein content of ECS components instead of transcript levels. Another study recently published by Gandhi et al ., showed that maternal HF diet in baboons decreases CB2 and FAAH protein content in fetal liver, but the impact of ECS changes on liver morphology and function was not investigated 48 . The different profiles found in liver ECS among these studies may arise from different ages and species used in the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evident role of the ECS in neurodevelopment, there are few studies on the implication of the endocannabinoid system in perinatal programming, most of which have focused on a hypercaloric diet and the alteration of cannabinoid receptors in the short and long term in offspring, specifically in the brain and peripheral tissues [13,[44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The tonus of the ECS in the brain and peripheral tissues may be modulated by unappropriated parental life style and environmental conditions (nutrition, toxicant exposure, and stress) during the perinatal period and adolescence, predisposing offspring to metabolic and behavioral disorders throughout life (Figure 6; Lopez-Gallardo et al, 2012;Stringer et al, 2013;Ramirez-Lopez et al, 2015, 2016aRomano-Lopez et al, 2016;Almeida et al, 2017Almeida et al, , 2019Almeida et al, , 2020Dias-Rocha et al, 2018;Gandhi et al, 2018;Miranda et al, 2018;de Oliveira et al, 2019;Soares et al, 2019;Rivera et al, 2020). This phenomenon is known as "metabolic programming" or "ontogenetic plasticity" and involves epigenetic regulation of gene expression (Brenseke et al, 2013;Lillycrop and Burdge, 2015;Gluckman et al, 2019).…”
Section: Programming Of the Endocannabinoid System During Early Lifementioning
confidence: 99%
“…Maternal high-fat (45% fat) diet decreases serum levels of eCBs in baboon offspring at birth (Gandhi et al, 2018). In rats, a maternal hypercaloric-low protein diet (6% protein, 24% fat) decreases hypothalamic endocannabinoid levels only in newborn male offspring, while decreases the preference for a chocolate diet and induces anxiety-like behavior in these animals in adulthood (Ramirez-Lopez et al, 2015, 2016a.…”
Section: Programming Of the Endocannabinoid System During Early Lifementioning
confidence: 99%